Investigating the Performance of Hard Rock Pillars with Different Width to Height Ratios and the Effects of Inclination, a Discontinuity and Blasting - Jessu, Kashi Vishwanath (Curtin University, 2018)
Pillar design, a challenge in underground hard rock mines, contributes to catastrophic failure or economic loss based on its failure mechanism. Factors influencing the pillar failure mechanisms such as pillar inclination, presence of discontinuity and blasting effects were investigated with the help of laboratory tests and numerical analyses to create a design structure. Lastly, the pillar designs were evaluated by developing strain based monitoring method for pillar classification and pillar optimization.